Improving Edge Quality of Liquid Crystal Display 3D Printing Using Local Dimming Method - Xing-Rui Ding; Zi-Hao Deng; Jia-Sheng Li; Rui-Xiang Qian; Bo-Wen Duan; Zong-Tao Li (IEEE Photonics Journal)
The burgeoning advancements in Light Emitting Diode (LED) technology have opened avenues for applications beyond traditional display and lighting, notably in the realm of 3D printing. This study introduces a Local Dimming (LD) method that employs LED backlight technology to enhance the edge quality of Liquid Crystal Display (LCD) photocuring 3D printing (LPP). LPP, known for its rapid and cost-effective fabrication, faces challenges with light leakage and precision under high-power ultraviolet (UV) light. By locally adjusting the backlight array's brightness to conform to the digital mask's shape, this study effectively suppresses LCD light leakage and improves edge definition. A comprehensive investigation into the LD method's process parameters—exposure time, pixel compensation coefficient, and initial backlight calculation—reveals significant improvements in print quality. The LD method achieves up to an 81.56% enhancement in dimensional accuracy compared to the conventional full-backlight technique. This research not only addresses the intrinsic light leakage in LCDs but also facilitates the high-resolution printing of complex structures, thus expanding the utility of LED devices in additive manufacturing.